(515) Some Pricing Problems of National Industry in the united Kingdom بعض مشاكل التسعير في الصناعة الوطنية في المملكة المتحدة - E. Watkin, E (INP, 2024)
The study discusses pricing problems in national industries in the United Kingdom, noting that these industries, like their counterparts in other countries, face stringent economic and financial obligations. They are expected to produce their goods and services efficiently, meeting consumer needs while minimizing production costs. Additionally, they are required to operate "in the public interest," as defined by the government and managers. Although nationalized industries hold a statutory monopoly, economic competition still exists, particularly from substitute products like oil. The taxation on certain oil fractions, such as diesel oil, is a major reason why the substitution of oil for coal has not progressed further in the UK, affecting the extent of this competition.